Effectiveness of corporate governance mechanisms: a review of the literature - Mat Yasin, Fatimah; Muhamad, Rusnah; Sulaiman, Noor Adwa (Faculty of Business & Accountancy, University of Malaya., 2016)
The key players in corporate governance worldwide are often associated with their potential for enhancing corporate governance practices. This paper presents a review of academic research concerning the effectiveness of these players. Given the importance of these key players, as emphasized by the regulators in most countries, it is crucial to explore their contributions, as documented in the literature. Hence, fundamental insights for analysing the inputs that contribute to their effectiveness, as well as the processes and the outcomes of their effectiveness are discussed in this paper. Furthermore, there is limited evidence that discusses the effectiveness of these players from the perspective of process issues. However, as such studies pertaining to the process issues are important for understanding how they actually perform their roles and enhance their effectiveness, more studies that focus on the process issues are suggested for future research to provide a better understanding of the effectiveness of key players.